INTEGRATION OF LABORATORY DATA IN PREDICTING THE EPIDEMIOLOGY OF DIABETES - Yodgorova Feruza Ibrohim kizi (Ethiopian International Journal of Multidisciplinary Research, 2026)
Diabetes mellitus is one of the most pressing global public health challenges, with its prevalence steadily increasing worldwide. Early detection, assessment of disease risk, and population-level prediction are essential for developing effective preventive strategies. The aim of this study is to evaluate the role of integrating laboratory data in predicting the epidemiology of diabetes mellitus. The results demonstrate that the comprehensive analysis of biomarkers such as glucose, HbA1c, insulin, lipid profile, C-reactive protein, and other indicators enables high-accuracy prediction of diabetes risk. An integrated laboratory model contributes to improving both individual and population-level risk stratification.